Application of the simple atrial fibrillation better care pathway for integrated care management in frail patients with atrial fibrillation: A nationwide cohort study - Pil‐Sung Yang; Jung‐Hoon Sung; Eunsun Jang; Hee Tae Yu; Tae‐Hoon Kim; Gregory Y. H. Lip; Boyoung Joung (Journal of Arrhythmia, 2020)
Abstract Background The benefit of integrated care management was unknown in frail atrial fibrillation (AF) patients. This study evaluated whether compliance with the atrial fibrillation Better Care (ABC) pathway for integrated care management would improve clinical outcomes in frail AF patients. Methods From the Korea National Health Insurance Service database, 262,987 nonvalvular AF patients were enrolled between 1 January 2005 and 31 December 2015. For each patient, the Hospital Frailty Risk Score and category were calculated retrospectively using all available ICD‐10 diagnostic codes. Patients were divided into three frailty‐based risk categories: low (<5 points, n = 221,542), intermediate (5‐15 points, n = 37,341), and high risk (>15 points, n = 4,104). Results Over a mean follow‐up of 5.9 (interquartile range 3.2, 9.4) years, in high frailty risk patients, the ABC group had lower rates of all‐cause death (6.5 vs 17.5 per 100 person‐years, P < .001; hazard ratio [HR] 0.74; 95% confidence interval [CI] 0.56‐0.97) but was nonsignificant for the composite outcome (10.5 vs 26.0 per 100 person‐years, P = .101; HR 0.79; 95% CI 0.59‐1.05) compared with the Non‐ABC group. When the three frailty categories were compared, the greatest benefit on mortality was seen in the high frailty group (pint < 0.001), but for the composite outcome, there was no statistical interaction for the three frailty categories (pint = 0.063). Conclusions Compliance with the simple ABC pathway is associated with improved outcomes in AF patients with high frailty risk. Given the high healthcare burden associated with frail AF patients, integrated AF management should be implemented to improve outcomes in these patients.